2022
DOI: 10.1109/tbme.2021.3119280
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-Angiogenic Chemo-Sensitization via Longitudinal Ultrasound Localization Microscopy in Colorectal Carcinoma Tumor Xenografts

Abstract: Super-resolution ultrasound localization microscopy (ULM) has unprecedented vascular resolution at clinically relevant imaging penetration depths. This technology can potentially screen for the transient microvascular changes that are thought to be critical to the synergistic effect(s) of combined chemotherapy-antiangiogenic agent regimens for cancer. Methods: In this paper, we apply this technology to a highthroughput colorectal carcinoma xenograft model treated with either the antiangiogenic agent sorafenib,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(74 reference statements)
0
10
0
1
Order By: Relevance
“… 19 , 29 , 45 , 73 The measurement is to examine how quickly these vibrations move through the organ, and then this information will be used to create a visual map revealing the differences in the elastic properties of soft tissues for further diagnosis. On the other hand, conventional ultrasound diagnostic images can only visualise the differences in soft tissue acoustic properties through the echogenicity of ultrasound waves passing through the soft tissue, 62 , 68 , 75 whereas ultrasound elastography (USE) images (Fig. 5 d) are able to reveal the differences in the elastic properties of soft tissues.…”
Section: Biomechanics Of Bowel Cancermentioning
confidence: 99%
“… 19 , 29 , 45 , 73 The measurement is to examine how quickly these vibrations move through the organ, and then this information will be used to create a visual map revealing the differences in the elastic properties of soft tissues for further diagnosis. On the other hand, conventional ultrasound diagnostic images can only visualise the differences in soft tissue acoustic properties through the echogenicity of ultrasound waves passing through the soft tissue, 62 , 68 , 75 whereas ultrasound elastography (USE) images (Fig. 5 d) are able to reveal the differences in the elastic properties of soft tissues.…”
Section: Biomechanics Of Bowel Cancermentioning
confidence: 99%
“…Due to the low cost, wide accessibility, and safety, ultrasound has the latent capacity to turn into the preferred method of cancer imaging. 80 Doppler ultrasound techniques or conventional B-mode are challenged to demonstrate microvascular characteristics on the scale of early tumor angiogenesis. ULM is not limited to diffraction-limited resolution, which makes this technique a potentially forceful technique.…”
Section: ■ Ultrasound Contrast Agentsmentioning
confidence: 99%
“…Early studies conducted by Viessmann et al [1], Desailly et al [2][3], and O'Reilly et al [4] showed that one can break the resolution limit of acoustic waves by localizing microbubbles in the blood stream. The seminal papers by Errico et al [5] and Christensen-Jeffries et al [6] catalyzed the growth of the field, leading to many subsequent reports with successful in vivo applications [7][8][9][10][11][12][13][14][15][16] and technical advancements of super-resolution ultrasound imaging [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%